Pembangunan dan Partisipasi Politik di Indonesia Pasca Orde Baru: Dari Teknokratis ke Populis? - Anwar Ilmar (Universitas 17 Agustus 1945 Jakarta, 2017)
This article is motivated by the emergence of a wave of democratic phenomenon that also hit Indonesia in the late 1990s. The wave of democracy had a strong influence on the emergence of the discourse of strengthening the political participation that was suppressed during the New Order era. The New Order state runs a development model that puts forward the economic aspect rather than politics. Many call it a technocratic development model. This development model is considered successful in carrying out development by adopting policies to tightly control political activities including people's participation in them. However, the formerly revered model of development, suddenly received strong criticism and opposition. Economic development only enjoyed a handful of elites and created social imbalances. In the post-new order era, political participation was enhanced through the strengthening of political parties and elections. The consequence is, the increased participation of the people in the activities of the state. Economic development is also aimed at equal distribution of income. The new post-order development model is often referred to as the populist model. This article concludes that post-New Order development does not fully show a populist model. This is marked by widening economic inequality and political power remains in the hands of a handful of elites such as in the New Order period. Keyword: Development, Political Participation, Technocratics, Populist